Cryo-EM structures of tau filaments. (October 2020) - Scheres, Sjors HW; Zhang, Wenjuan; Falcon, Benjamin; Goedert, Michel
Highlights: Cryo-EM may be used to determine atomic structures of amyloid filaments extracted from human brain tissue. Unique protofilament folds characterise tau filaments from different neurodegenerative diseases. In vitro assembly of recombinant tau with heparin leads to different filaments from those observed in disease. Isoform composition, post-translational modifications or co-factors may drive structural specificity of tau assembly. Abstract : Assembly of microtubule-associated protein tau into filamentous inclusions underlies many human neurodegenerative diseases, called tauopathies. Tau inclusions display distinct cellular and neuroanatomical distributions in different tauopathies. Morphological and biochemical differences suggest that tau filaments adopt disease-specific molecular conformers, similar to prion strains. Breakthroughs in electron cryo-microscopy have recently yielded atomic structures of tau filaments extracted from the brains of individuals with various tauopathies. Each disease is characterised by a unique tau filament fold, which is conserved among individuals with the same disease. In vitro aggregation yields different structures from those observed in brain. Tau isoform composition, post-translational modifications or interactions with cofactors may determine which structures are formed in brain. Understanding filament formation will be central to deciphering the molecular mechanisms that underlie human tauopathies.